Student Luggage Storage System (SLSS) / Sofea Aida Sallehan - Sallehan, Sofea Aida (2020)
Student Luggage Storage System (SLSS) is a prototype of a room booking system that provide students with room or space to store their personal belongings during semester break and it is being developed for the students of UiTM Cawangan Terengganu Kampus Kuala Terengganu (UiTMCTKKT). This system is proposed as an alternative for the students to book the room and for the house owner to make a room rental service. The development of this system is based on the current business process. Students faced few difficulties to find a space to put on their personal belongings during the end of semester. The objective of this system is to identify current process and problems with the current system, to design and develop a system for both user requirements and system requirements and to evaluate functionality and usability of the system. Users that involved in this system are students, house owner and staff of Kerawang College. The method to build this system is System Development Life Cycle (SDLC). To achieve the outlines of the objectives, there are six phases to be used in the project framework. The six phases are planning, analysis, design, development, implementation and testing and documentation. The system has been tested and evaluated using test plan, scenario and user evaluation from four representative users. The metrics used for the usability testing is recommended by the International Organization for Standardization (ISO). It is based on effectiveness, efficiency and satisfaction metrics. Based on the findings, the system is falls under the range of acceptable which means it is ideal to be use by the users. It is hoped that SLSS can enhance the flow of the current business process for both students and house owner.